Terrorist learning: a new analytical framework - Kettle, Louise; Mumford, Andrew (Taylor & Francis, 2017)
Terrorists learn every day to gain further knowledge on how to achieve their violent objectives. Consequently, understanding terrorist learning forms a crucial part of the fight to counter terrorism. However, whilst existing literature within terrorism studies has examined a number of different parts of the learning process there currently fails to exist a comprehensive framework to encompass the learning process as a whole. This article will rectify this oversight by drawing upon wider learning literature to develop a new analytical framework for terrorist learning that provides a definition, considers the actors involved and identifies processes and outcomes. Consequently, the full landscape of current and potential research in this important area is revealed.